Policies and Incentives Offered by the Top Ten American States in Biotechnology that Promote Start-Up Activities - D. Kamat, Kalika; J. Crawford, Daniel; J. Leslie, George; Zhang, Maomao; Jiang, Qinqin; K. Gupte, Rohit; A. Tsai, Ellen; B. Reitz, Allen (Technology Transfer and Entrepreneurship (Discontinued), 2014)
The biotechnology industry in the United States is comprised of more than 1,300 companies. During the decade between 2001 and 2010, biotech in the U.S. was one of the few industries that grew, at a rate of 6.4% annually. However, this growth was distributed non-uniformly across the U.S., with some states attracting more biotechnology startup ventures than others, even when normalized for the population living in those states. Many factors contribute to why certain regions of the U.S. have a more developed biotechnology industry than others. For example, the presence of venture capital and investment banking firms as well as the presence of a trained workforce of former pharmaceutical industry personnel are “fixed assets or variables” that promote biotech entrepreneurial activities. We here seek to study in particular the role that individual state-wide incentives or “discretionary public policy variables” play in attracting biotech entrepreneurs to those states, which could be considered as general strategies to be applied to other states seeking to expand economic activity in this sector. To this end, we analyzed where funding was awarded per U.S. state from the Qualifying Therapeutic Discovery Project Credits and Grants Program (QTDP) of the U.S. Patient Protection and Affordable Care Act of 2010, both in terms of absolute dollar amounts and amount per capita being normalized for the total population in each state. Using this approach, we identified the 10 top U.S. states where biotechnology research was the most developed which are Massachusetts, Maryland, California, New Jersey, Washington, Utah, Rhode Island, Colorado, Minnesota, and Connecticut. A qualitative analysis of the activities in each of these 10 states was conducted to examine the discretionary public policy variables that promoted entrepreneurship in the biomedical research area.
Keywords: entrepreneurship